Pre-service science teachers’ cognitive structures regarding science, technology, engineering, mathematics (STEM) and science education * - Hacıoğlu, Yasemin; Yamak, Havva; Kavak, Nusret (Journal of Turkish Science Education, 2016)
The aim of this study is to reveal pre-service science teachers’ cognitive structures regarding Science, Technology, Engineering, Mathematics (STEM) and science education. The study group of the study consisted of 192 pre-service science teachers. A Free Word Association Test (WAT) consisting of science, technology, engineering, mathematics and science education concepts and semi-structured interview records were utilised to reveal their opinions regarding these concepts and inter-conceptual relations were used as data collection tools. While the WAT was implemented with all of the pre-service teachers, semi-structured interviews were carried out with only eight of the pre-service science teachers. Using two data collection tools via triangulation, enabled the researchers to obtain similar and varied findings. According to the frequencies, WAT was analysed using the cut-off point (CP) method; hence, concept network maps were composed and interviews were descriptively analysed. The findings of the study revealed that pre-service teachers’ cognitive structures involved STEM disciplines and science education were quite independent from each other. Also, they could not make a distinction between science concept and science education concept, nor associate ‘technology, engineering and mathematics’ concepts with science and science education’ concepts.
Keywords: Cognitive Structure; Pre-service Teachers; STEM; Science Education; Word Association Test